EFEKTIVITAS PROGRAM PEKARANGAN PANGAN LESTARI (P2L) DI DESA MEKARJAYA KECAMATAN BAITO KABUPATEN KONAWE SELATAN - Lulu Hikmawati; Hartina Batoa; Yoenita Jayadisastra; Darsilan Dima (Jurusan Penyuluhan Pertanian FP UHO, 2025)
This study aims to determine the effectiveness of the sustainable food garden program (P2L) in supporting food security in Mekarjaya Village, Baito District, South Konawe Regency. The population in this study consists of all farmers participating in the P2L program, totaling 30 farmers. The sample was determined using the census method, i.e., all farmers. The study location was selected using the purposive method, i.e., deliberate selection. The study was conducted in Mekarjaya Village because this village has an optimally implemented Sustainable Food Garden Program (P2L). The analysis method used was quantitative descriptive analysis with the assistance of an effectiveness formula. The results of the study indicate that the P2L program is quite effective, particularly in terms of program understanding and tangible changes, but there are still challenges in terms of target accuracy and the sustainability of impacts.